Implementation and Impact of Business Ethics Policy on Corruption in Banking Institutions in Bangka Belitung: A Study from Legal and Managerial Perspectives - Sari, Patricia Widya (International Journal of Magistravitae Management, 2024)
This research examines the implementation of business ethics policies from two main perspectives: legal and managerial. Specifically, business ethics policies in banking institutions are designed to prevent corruption by enforcing strict behavioral standards. This study evaluates how effectively these policies are implemented and how they contribute to reducing corruption. From a legal perspective, the research analyzes the compliance of business ethics policies with applicable laws and regulations, including the effectiveness of legal sanctions for violations. It also identifies the strengths and weaknesses of law enforcement related to business ethics policies in banking financial institutions. From a managerial perspective, the study assesses the impact of business ethics policies on organizational culture and employee behavior. Additionally, it examines how these policies influence managerial decision-making, risk management, reputation, and public trust in banking financial institutions. While business ethics policies have a positive impact on reducing corruption, challenges in legal enforcement and managerial implementation persist, necessitating continuous improvements to enhance policy effectiveness. The findings of this study are expected to provide recommendations for improving business ethics policies and practices to strengthen integrity and compliance within banking financial institutions in Bangka Belitung.